Os impactos da revolução digital na indústria da comunicação - Villegas, Greicy Marianne Lopes Guimarães Cahuana (2016)
With the technological advances of the last decade, sets up a new world. In this new scenario, change people and their daily life, mediated by new tools. New modes of interaction bring with them new possibilities, as well as new challenges. The research object deals with the advertising hybridization process, combined with the interactivity and distribution possibilities via sharing. We had as objective to describe and analyze the breaks of the current advertising model, the transitions of creative and production processes and trends in the communications industry in their new settings. The panorama of the advertising market is moving. On one side advertisers seeing their investments in communication falling in efficacy compared to a few decades ago and demanding new solutions to their agencies. On the other agencies, which until the other day felt comfortable to hold campaigns in the traditional format, looking for these new solutions, It is not enough to combine more creativity to the purchase of space on TV channels most watched and magazines wider audience. Today every advertising agency is faced with the same challenge: to create integrated campaigns in different formats involving multiple digital tools, that add value to the brand and reach a consumer increasingly demanding and participatory. In view of this we have the following cases: media convergence and the interactions of the media environment generate new advertising settings, incorporation into the advertising language elements such as entertainment and interactivity lead to hybridization between those elements and the original functions of advertising, which are to inform and persuade; the hybridization strategies of advertising language lead in persuade, making it a new media product, advertising entertainment and interactive advertising. In the investigation of these hypotheses in the fundamentals in various theoretical concepts and authors such as Pierre Lévy, Henry Jenkins, Martha Gabriel, Ricardo Ramos, Rogério Covaleski. There is much to be done so that the full potential of interactive media is maximized by agencies and advertisers. These need to be alert the changes that are occurring and prepared to adapt their services to this new reality, acting with competence and effectiveness. Competitive advantage will be in the hands of those who mobilize in order to meet new market demands .So, to win the market is crucial both the training of professionals who provide specialized services for advertising agencies, as the appropriate technologies for the use of interactive language. Some advertising agencies in Brazil are already adjusting to the changes required by digital technologies, thus bring cases of successful placements that take advantage of the great potential of these media